Characterization and Analysis of 2-(2-Phenylethyl)chromone Derivatives and Sesquiterpenoids from Agarwood of Four “Qi-Nan” Clones (Aquilaria sinensis) with Different Induction Times - Ming Li; Zhou Hong; Shengjie Wang; Daping Xu; Zinong Yang; Zhihui Li; Houzhen Hu; Suxin Li (Molecules)
In recent years, some new “Qi-Nan” clones of Aquilaria sinensis with the characteristics of easy induction and high-quality agarwood have been obtained, through the cultivation and propagation of grafted seedlings. These clones are used for the intensive production of high-quality agarwood. The speed of resin formation and yield are crucial for the development of the agarwood industry. The differences in yield and chemical composition among different Qi-Nan clones and induction times are worth investigating. While the chemical composition differences between Qi-Nan and ordinary A. sinensis have been extensively studied, the effects of induction time coupled with different Qi-Nan clones on the chemical composition of Qi-Nan agarwood remain insufficiently explored. This study compared the changes in the chemical composition of four “Qi-Nan” clones of A. sinensis after 6, 12, and 24 months of induction through GC-QTOF-MS, the chemical composition and structure types of the four “Qi-Nan” clones were mainly 2-(2-phenylethyl)chromone derivatives (PECs) and Sesquiterpenoids (SESs), with the prolongation of induction time, the content of SESs increased, while the content of PECs decreased. Both the differences among clones and the induction time of “Qi-Nan” agarwood influence its chemical composition, which in turn affects the quality of the agarwood. Among these factors, induction time has a greater impact on the production of PECs in agarwood. The prolongation of induction significantly enhanced the yield of “Qi-Nan” agarwood and exhibited an inducing effect on the production of 2-(2-phenylethyl) chromone and 2-(2-4 phenylethyl)chromone. Compared with the agarwood obtained after 6 and 12 months of induction, the agarwood of “Qi-Nan” after 24 months of induction exhibited superior quality. The induction time for high-quality agarwood from the XGY clone was shorter (12 months) compared to the RH, YYZ, and AS clones (24 months). The study underscores that optimizing induction time and selecting suitable “Qi-Nan” clones can significantly enhance agarwood yield, quality, and production efficiency.